STRATEGIES FOR NEW INTERNATIONAL VENTURES IN THE BRAZILIAN SUGARCANE INDUSTRY: THE CASE OF ETH BIONERGIA - Marina Carrilho Soares; Heidy Rodriguez Ramos (Future Studies Research Journal: Trends and Strategies, 2010)
This study aims to identify cases of new international ventures in the Brazilian sugarcane industry, specifically as regards ethanol production, i.e., companies that are established from start to have an international profile. The paper explores the case of one such enterprise in the light of the theories addressed. In the last few years, a rising number of companies with this profile have appeared. This runs contrary to the main classical theories of internationalization, which present this process as evolutionary. As for the sugarcane industry, it has expanded considerably in recent years, which led many groups to invest in this segment. This study is a descriptive, qualitative piece of research and is based on the case study of a company recently established in this sector. Analyzing the chosen organization and comparing it to the studied theories, the authors concluded that there is, indeed, a type of organization with the profile of a new international venture. Key-words: Internationalization. New international ventures. Sugarcane industry. Brazil.